Social Welfare of Rural Communities as a Function of Social Workers’ Empowerment - Kurniasih, Dewi; Anjani, Maisya Chaluela (Journal of Ethnic and Cultural Studies, 2025)
Social workers play an important role in uplifting rural communities’ living standards. Considering the important role of social work services in dealing with the existence of potential issues of poverty and poor economic conditions in rural communities, more specifically in emerging economies, the current study integrated the community-based targeting view with empowerment theory to determine the social workers’ role in achieving community welfare in rural areas. Using rural household survey data from 597 households from 15 rural communities in two provinces of Indonesia, modern statistical tools, that is, SmartPLS analyzed the data. Results showed that social workers’ work relationships, skills and varieties, and moral alignment with rural communities enhance their empowerment qualities. The empowerment of social workers further transmits the significance of their role in helping rural communities bring economic development and welfare by providing basic needs of education, health facilities, employment opportunities, etc. The current study findings are valuable for practitioners and policymakers, specifically for focusing on rural community development programs by utilizing social workers’ efforts and extending their social networks to extract maximum benefits.